PEMBINGKAIAN (FRAMING) ISU OLEH PEMERINTAH RUSIA TERHADAP KELOMPOK SEPARATISME CHECHNYA PASCA 9/11 - SARI, CUT FITRI INDAH ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This paper aims to investigate the reasons behind the efforts undertaken by framing the issue of the Russian government against the Chechen separatist groups. The issue is framed is separatism which is then framed into the issue of terrorism. Framing itself is done after 9/11 that occurred in the United States and around the world constructed will result in the issue of terrorism, including the Russian government itself. Analyzer used in this paper is the concept of framing which includes understanding the framing, the objectives of the framing, and how the stages of the process of framing is done. The results of the research in this paper is the reason the Russian government do the framing of issues against Chechen separatist group is to defend its national interests over Chechnya. National interests, among others is to legitimize the war that began in late 1999 Russia and interests to gain the support of the international parties.